Гибкие фольгированные диэлектрики: классификация и анализ направлений применения и совершенствования - Vorobyev, A. V.; Zhora, V. D. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
The paper presents a classification of flexible foiled dielectrics of different types. A comparative analysis of the properties of dielectrics manufactured with the use of adhesives, as well as without them, is given. Methods for the preparation of flexible foiled non-adhesive dielectrics, materials of conductive layer and a dielectric base are considered. The technical characteristics of the various polymer films used as a dielectric base are given. The advantages of the polyimide films in comparison with other polymer films are shown.The most perspective option of manufacturing of non-adhesive foiled dielectrics based on polyimide obtained by applying of a polyimide lacquer on metal foil, the so-called lacquer-foil dielectrics, is highlighted. The technology of manufacturing of lacquer-foil dielectrics with higher quality characteristics is described. The polyimide base of dielectrics has better adhesion to the foil and guaranteed uniformity of degree of imidization of 95–100%. The technology developed has allowed to carry out serial production of materials for electronic equipment. A series of lacquer-foil dielectrics of different thicknesses of foil is manufactured: aluminium — 10, 14, 20, 25 and 30 µm, nickel — 7 µm and copper — 18, 35, 50 µm. These materials are used for the manufacturing of flexible polyimide carriers, stubs, microcables, membranes of acoustic transducers and thermistors.